Does Deforestation Trigger Severe Flood Damage at Hoeryeong City in North Korea? - Joongbin Lim (Forests, 2019)
North Korea has suffered flood damage every year since 1995. It is assumed that this damage is linked to deforestation. Therefore, the purpose of this study was to investigate the effects of deforestation on the occurrence of floods in North Korea using spatial statistical techniques. The research was conducted at Hoeryeong City, which experienced disastrous flooding in 2016. A land-use change map was produced using two Landsat data sets from 1977 and 2016. The flood-damaged areas map, landform map, and the distance from the nearest stream map were also used in the spatial statistical analysis. In the deforestation zone, area of soil loss over 200 tons/yr increased by 14 km2 (16.6%), while that under 50 tons/yr decreased by 25 km2 (29.3%). In addition, the land-use change, runoff coefficient, and peak time runoff increased from 0.31 to 0.46, 56.3 mm/hr to 60.8 mm/hr, and 128.2 m3/sec to 206.6 m3/sec, respectively. Also, spatial statistical analysis results showed that land-use change was concluded to strongly affect the occurrence of floods. In conclusion, deforestation at Hoeryeong City contributed to severe flooding due to changes in land-use policy. The results of this study will help decision makers to establish the North Korean forest restoration policy and countermeasures against flood damage.